Chemical constituents of the medicinal plant Indigofera spicata Forsk (Fabaceae) and their chemophenetic significance. (April 2021) - Mouafon, Iliassou L.; Tiani, Gesquiere Laure M.; Mountessou, Bel Youssouf G.; Lateef, Mehreen; Ali, Muhammad S.; Green, Ivan R.; Ngadjui, Bonaventure T.; Kouam, Simeon F.
Abstract: The chemical investigation of the whole plant of Indigofera spicata Forsk (Fabaceae), a medicinal plant from Cameroon, resulted in the isolation of a new benzofuran, named spibenzofuran (1a), together with ten known secondary metabolites including one benzofuran (2 ), one flavonoid (3 ), one saponin (6 ), two triterpenes (4 and 5 ), two steroids (8 and 11), one phthalate (7 ) and two fatty acids (9 and 10 ). All these compounds have been isolated for the first time from this plant. The structures of the isolated compounds were established by spectroscopic analysis including HR-ESI-MS, 1D and 2D NMR and by comparison of our data with the reported data. The isolated compounds might be considered as the chemophenetic markers of this species, and antibacterial and urease inhibitory activities of some isolated compounds were assessed. Graphical abstract: Image 1 Highlights: A new benzofuran from Indigofera spicata Forsk. Structure elucidation with NMR and MS analyses. Antibacterial and urease activities of isolated compounds. Chemophenetic significance of the isolated compounds.